THE DIFFERENCE OF COGNITIVE LEARNING OUTCOMES BETWEEN STUDENTS WHO LEARNED BY USING PROBLEM SOLVING AND PROBLEM POSING LEARNING MODEL IN SALT HYDROLYSIS MATERIAL - Dian Eka Wati; Arif Sholahuddin (PROSIDING SEMINAR KIMIA, 2015)
This study aims to determine the differences of conceptual understanding, problem-solving skills, and to know the students’ response to implementation of problem posing and problem solving learning model in salt hydrolysis material. This quasi-experimental research used pre-test-post-test comparison group design were took place at class XI student of SMAN 6 Banjarmasin. By using t-test analysis, this research showed that there are differences in conceptual understanding and problem solving skills significantly between students learned by using problem posing and problem solving learning model. The students’s cognitive learning outcomes who learned by using problem posing better than who learned by using problem solving learning model. Students gave a positive response to implementation of the both learning models.